Understanding the linkages between male circumcision and multiple sexual partnership among married Ghanaian men: Analysis of data from the 2014 Ghana demographic and health survey - Bright Opoku Ahinkorah; John Elvis Hagan, Jr; Abdul-Aziz Seidu; Eric Torgbenu; Eugene Budu; Thomas Schack (Elsevier, 2020)
Introduction: This current study sought to investigate the association between male circumcision status and engaging in multiple sexual partnership among men in Ghana. Methods: Data from this study come from the men's file of the 2014 Ghana demographic and health survey. Both descriptive and inferential statistics were conducted among 1, 948 men and the level of statistical significance was pegged at p < 0.05. Results: Results revealed that men who have been circumcised were more likely to engage in multiple sexual partnership (AOR = 3.36; CI:1.14-9.89), compared to those who have not been circumcised. With the covariates, men with primary level of education were more likely to have multiple sexual partners (AOR = 2.01; CI:1.10-3.69), compared to those with no education. With wealth status, men with richest (AOR = 2.27; CI:1.04-4.97), richer (AOR = 2.05; CI: 1.03-4.08), and middle wealth status (AOR = 1.83; CI:1.01-3.34) had the highest likelihood of having multiple sexual partners, compared to those with poorest wealth status. Conversely, men who professed the Islamic faith were less likely to engage in multiple sexual partnership (AOR = 0.58; CI: 0.36-0.94), compared to Christians. Similarly, men who resided in the Brong Ahafo (AOR = 0.51; CI: 0.26-0.99), Upper East (AOR = 0.41; CI:0.19-0.89), and Ashanti regions (AOR = 0.39; CI: 0.20-0.78) were less likely to engage in multiple sexual partnership. Conclusion: Based on the current findings, educational campaigns by stakeholder groups (e.g., Ministry of Health in collaboration with the National Commission on Civic Education, civil society, educational institutions) should sensitize the sexually active population at the community level to consistently use condoms, especially when they have multiple sexual partners, even when a man is circumcised. Campaign messages must clearly emphasize that male circumcision should not substitute precautionary measures such as delay in the onset of sexual relationships, averting penetrative sex, reducing the number of sexual partners as well as correct and consistent use of male or female condoms regardless one's social standing.